"Post COVID 19- Economic Opportunities & Challenges in India: Crisis that led to innovations and the road ahead" - Prof. Mezbin Lalani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
COVID 19 pandemic has shook all the economies around the globe with India being no exception to this. COVID 19 and the year 2020 will be remembered in history not just as the year of the pandemic and the crisis that followed but also for the innovations which we witnessed especially in the healthcare industry and the manufacturing sector. Thus, this crisis has brought with itself a wide array of opportunities. This research paper highlights the various innovations that India saw in this pandemic and the road ahead post COVID.